Development of a Computer-Based Information System at SMA Negeri 1 Lawe Sigala-gala - Marsya, Jiwa Malem (Literacy: Journal of Education and Social Science, 2025)
Information systems (IS) are critical for the effective management of educational institutions. This study develops a computer-based information system (CBIS) at SMA Negeri 1 Lawe Sigala-gala to improve data management, administrative efficiency, and decision-making. The system integrates student, teacher, curriculum, and financial data into a centralized platform, supporting planning, organizing, leadership, and control functions. Feedback from teachers, staff, and students shows increased operational efficiency, reduced manual workload, and improved digital literacy. This research contributes to understanding the practical implementation of IS in schools under regional autonomy and provides recommendations for future improvements.